PERSAINGAN USAHA DALAM PERSPEKTIF HUKUM EKONOMI KONVENSIONAL DAN EKONOMI SYARIAH - Mohamad Tedy Rahardi (PERADA, 2018)
This study focused on the comparative study of the principles of business competition in conventional economics and Sharia economics. It was generated by the phenomena of business competition which increasingly leads to global business competition, thereby reducing the meaning of business competition for domestic areas. In this study it is known that global competition trends lead to liberal economic systems that want markets to be free. In the study of conventional economic law, this competition leads to free competition that brings the market mechanism to the market itself with the role of the government as supervisor when there is a violation on that fair competition. Whereas in the study of sharia economic law, the discourse on the market supervisory board (hisbah) becomes an important part of the market structure and mechanism, there by embodying fair competition and the consumer community is not burdened by unfair practices. Thus, both of them have similarities in market mechanisms, but differ in looking at the role of market structure.